PENGEMBANGAN BAHAN AJAR DIGITAL MATEMATIKA DENGAN BOOK CREATOR UNTUK MENDUKUNG PEMAHAMAN KONSEPTUAL PADA MASALAH ARITMATIKA SOSIAL - Muhammad Kafabihi Abdillah; Ulumul Umah; Dian Novita Rohmatin (SIGMA, 2023)
Social arithmetic is a useful topic for mastering numeracy skills that are useful in solving real-world problems. However, students' difficulties in solving social arithmetic problems are still found. In addition, the limitations of available digital learning resources are also an obstacle for some teachers. This article aims to describe the process and results of developing digital mathematics teaching materials with the Book Creator applications to promotes students' understanding of concepts in social arithmetic. The development of this teaching material is based on the ADDIE model with the following stages: analysis, design, development, implementation, and evaluation. Based on the conceptual understanding test on 6 subjects with various mathematical abilities, the average achievement result was 89%. The advantage of this teaching material is that it contains contextual problems that are in accordance with real-life situations, but on the other hand it is still necessary to develop more open-ended questions. This teaching material also contains questions for self-reflection to facilitate self-regulation in learning. For further development, teaching materials also need to be improved in terms of appearance, scope of lesson topics, and practicality in terms of collecting student written answer documents.